Geophysical study in En Nuhud basin area - Elmansour, Asim Abubabakr; Attag Omar, Omar (International Journal of Advanced Geosciences, 2018)
Integration of gravity, magnetic, resistivity and geophysical well logging methods were used to reveal the geological structures and the hydrogeological conditions. Magnetic mineralogy among the primary bed rocks or within the sedimentary sequence considerably affect the responses of gravity and magnetic methods. En Nuhud Basin is structural depression as a half-graben produced by displacement along a system of faults. Gravity measurements give a sense of that the area was dissected by different fault trends of NNW-SSE and E-W trends, with down throws towards the center of the basin, and variable magnitudes of displacement. The thickness of the sediments occupying the basin vary from few meters at the periphery of the basin to about 1000 meters at the southern parts. The water saturated zones in the Nubian Formation show good characteristics and a thickness range from 12- 140 m. The weathered Basement Complex is sometimes serve as aguiferous zone.